A Case of Tubo - Ovarian Actinomycosis - Beksaç, Mehmet Sinan; Kaya, Dilek; Çetinkaya Şardan, Yeşim; Usubütün, Alp (Gynecology Obstetrics & Reproductive Medicine, 2012)
We presented a case of tubo-ovarian actinomycosis in a patient with an intrauterine device (IUD). The patient was referred to our clinic with a diagnosis of pelvic inflammatory disease. Magnetic resonance imaging analysis indicated a cystic lesion (6.6x8x8 cm) on the left over. After performing total abdominal hysterectomy and bilateral salpingo-oopherectomy, histopathological studies showed a tubo-ovarian abscess and typical sulphur granules surrounded by neutrophils associated with actinomycosis. This case indicated that if clinicians are aware of actinomycosis in patients using IUCDs, the formation of tubo-ovarian abscess and thus excessive surgical procedures can be prevented.